MARKETING STRATEGY MODEL IN IMPROVING MARKETING PERFORMANCE (CASE STUDY OF CENTRAL SMALL INDUSTRY AREAS OF CENTRAL CIBADUYUT FOOTWEARS) - et. al., Keni Kaniawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Marketing performance is very important for a company, namely to measure the company's performance in the market for a product. Marketing performance in the industr i small and medium entrepreneurs Cibaduyut centers footwear Bandung, West Java decreased drastically. To provide alternati f solutions to those problems, it is important to do research to determine the variables that affect performance footwear marketing entrepreneurs in Cibaduyut, West Java. This study aims to analyze a marketing strategy model that can be implemented in marketing performance in the small and medium-sized industrial business area of footwear entrepreneurs in the center of Cibaduyut, Bandung, Indonesia.The analysis used is descriptive analysis to variab el qualitative da n analysis of the verification as a measure of hypothesis by using test statisti k for things that have causality. The analytical tool used is Sturktural Equation Models ) with the unit of analysis a d ne footwear entrepreneur Cibaduyut centers. The number of samples was 270 r respondents . The results of the study concluded that segmenting, targeting, positioning and digital marketing have an influence on the marketing performance of the Cibaduyut center footwear entrepreneur. But the influence of digital marketing on marketing performance has a negative effect. This is the finding of this study.